Menstruation Hygiene Practice Among Adolescent Girls - Neupane, Ishwor Prasad (ILAM इलम, 2023)
This study was based on menstrual hygiene practises among adolescent girls studying at Yubak Secondary School, Paknajol Ward No. 16, Kathmandu. Unhealthy menstrual hygiene is linked to significant morbidity and mortality due to reproductive tract infections (RTIs) and cervical cancer. This study was based on a descriptive research design. Open-ended and closed-ended questionnaires were used for data collection. The study was among 120 adolescent girls studying in grades 8, 9, and 10. Among them, 21% used to change pads daily, 33% used to change pads twice a day, 33% used to change pads when it got wet, and 13% used to change pads when they felt essential. Regarding the provision of a separate toilet for girls, 96% of adolescent girls said that there was a separate toilet for them. Regarding challenges faced by girls during menstruation at home and school, 38% were facing personal challenges, 38% were facing familial challenges, 8% were facing problems due to superstition, and 16% were found to be affected by sociocultural factors.